Kontribusi Hadis dalam Pembentukan Etika Konsumsi dan Produksi Berkelanjutan dalam Ekonomi Syariah - Nadia Sa’adah; Annisa Ariani; Hamdiah Hamdiah; Norhayati Norhayati; Norfitria Norfitria; Erwan Setyanoor (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The role of hadith in Islamic economics holds fundamental significance, particularly in shaping the ethics of consumption and production rooted in Islamic spiritual and moral values. In the face of increasing consumerism and unsustainable production systems, the sayings of Prophet Muhammad peace be upon him offer practical guidance that emphasizes simplicity, honesty, and social responsibility. This study employs a literature review approach to explore the contribution of hadith in constructing an economic system that is not only halal but also ethical and sustainable. The findings indicate that integrating hadith values into economic activities can serve as a normative solution to contemporary economic challenges.